ANALISIS FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN DAERAH KABUPATEN/KOTA DI JAWA BARAT - Satri Yani; Rifki Khoirudin (Optimum: Jurnal Ekonomi dan Pembangunan, 2020)
Autonomy in Indonesia is a form of government that the system changes centralization to decentralization. The existence of this decentralization is expected to accelerate the organization of public wealfare, as local goverments will be able to manage the financial resources of the region independently for welfare. This study aims to determine the effect of capital expenditure, general allocation funds, special allocation funds and local original income. The population in this study were all district and town in the province of West Java. The sampling technique used purposive sampling method and obtained 108 samples from 27 counties and cities of West Java in the years 2014-2017. Analysis toll using panel data regression analysis use of e-views 9. The results of this study indicate that capital expenditure, general allocation fund, earmarked grants and local rvenue simultaneously affect the interes and partial capital expenditure, general allocation fund, earmarked grants and local revenue positive effect on financial performance.